2020
DOI: 10.1071/wf20036
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlates of forest and land fires in Indonesia

Abstract: Biomass fires in Indonesia emit high levels of greenhouse gases and particulate matter, key contributors to global climate change and poor air quality in southeast Asia. In order to better understand the drivers of biomass fires across Indonesia over multiple years, we examined the distribution and probability of fires in Sumatra, Kalimantan (Indonesian Borneo) and Papua (western New Guinea) over four entire calendar years (2002, 2005, 2011 and 2015). The 4 years of data represent years with El Niño and La Niñ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 59 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…Our results resonate with other studies that focus on fire distributions in the EMRP area and the surrounding Indonesian peatlands, showing anthropogenic drivers to be the major contributing factors both in terms of the distance to infrastructural variables, and the impact of disturbed land‐cover classifications (Cattau et al., 2016 ; Tan et al., 2020 ; Vetrita & Cochrane, 2019 ). In contrast to the findings of Prayoto et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results resonate with other studies that focus on fire distributions in the EMRP area and the surrounding Indonesian peatlands, showing anthropogenic drivers to be the major contributing factors both in terms of the distance to infrastructural variables, and the impact of disturbed land‐cover classifications (Cattau et al., 2016 ; Tan et al., 2020 ; Vetrita & Cochrane, 2019 ). In contrast to the findings of Prayoto et al.…”
Section: Discussionsupporting
confidence: 91%
“…However, our findings do support the assertion that unmanaged swamp shrubland that occupies areas of degraded or cleared swamp forest is the most susceptible to fires (Miettinen et al, 2017;Prayoto et al, 2017;Sumarga, 2017;Thoha et al, 2018;Vetrita & Cochrane, 2019). Our findings also agree with the assertion that plantation concessions are not significant sources of fires (Cattau et al, 2016;Prayoto et al, 2017), though as Tan et al (2020) point out in their analysis, we have not accounted for the impact of plantations to the surrounding area, which may become evident if proximity to plantations were included. Contrary to the findings of Thoha et al (2018) we found peat depth within peatlands to be a relatively weak indicator of fire prevalence, which may be an important consideration as there is currently legislation that prohibits certain practices only on deep peatland (>3 m) (Uda, 2020).…”
Section: Interpretation Of Model Performance and Structuresupporting
confidence: 82%
“…Any restoration strategy for tropical peatlands must therefore incorporate fire prevention alongside rewetting, revegetation and the promotion of appropriate livelihood strategies. Multiple social drivers are at the root of the tropical peatland fire phenomenon (Santika et al, 2020;Sze et al, 2019;Tan, Carrasco, et al, 2020) and in order to limit fire occurrence, holistic restoration strategies will be needed to maintain and enhance any remaining natural forest cover and condition while also develop alternative non-burning methods for land management, raise public awareness and promote behavioural change (Harrison et al, 2020).…”
Section: Restoration Efforts For Livelihoods and Improved Socio-economic Outcomesmentioning
confidence: 99%
“…Spatiotemporal limitations in variables used in the models can also influence the estimates of restoration benefits and costs. For example, fire risk reduction was based on a dry El Niño year, despite differences in fire risks between dry and wet years (Tan et al 2020). The frequency and intensity of droughts and the risks of fire are likely to increase due to climate change (Turetsky et al 2015), hence projected fire risk reduction in the current paper can be viewed as conservative.…”
Section: Discussionmentioning
confidence: 99%